The 34th Conference of German Legal Historians in Würzburg (South Germany) 8th – 12th September 2002 - Gergen, Thomas (Cuadernos de Historia del Derecho, 2003)
From the 8th to the 12th of September 2002, the law historians in German language gathered in Wurtzbourg. These 34th History Journeys about Law, studied not only roman and medieval law but also the modern history of private law. Besides, an important place was reserved to the development of law in Eastern Europe, and to the investigations about law in former Democratic Republic of Germany.